Stability of food neophobia from infancy through early childhood. (1st February 2016) - Moding, Kameron J.; Stifter, Cynthia A.
Abstract: The purpose of the present study was to examine whether rejection of novel foods during infancy predicted child behavioral and parent-reported neophobia at 4.5 years of age. Data for the present study were drawn from a longitudinal study following individuals ( n = 82) from infancy through early childhood. At 6 and 12 months of age, the infants tasted a novel food (green beans, hummus, or cottage cheese) and their reactions were coded for rejection of the food (i.e. crying, force outs, or refusals). The children returned to the laboratory at 4.5 years of age and participated in a behavioral neophobia task where they were offered three novel foods (lychee, nori, and haw jelly) and the number of novel foods they tasted was recorded. Mothers also reported their own and their children's levels of food neophobia. Regression analyses revealed that rejection of novel foods at 6 months interacted with maternal neophobia to predict parent-rated child neophobia. Infants who exhibited low levels of rejection at 6 months showed higher levels of parent-rated neophobia when their mothers also showed high compared to low levels of neophobia. At 12 months of age, however, infants who exhibited high levels of rejection tended to have high levels of parent-rated neophobia regardless of their mothers' levels of neophobia. These results provide preliminary evidence that rejection of novel foods during infancy does predict neophobia during early childhood, but the results vary depending on when rejection of new foods is measured.